2019
DOI: 10.5430/ijfr.v10n5p228
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trade Liberalization in Carbon Dioxide Emission: Evidence From Heterogeneous Panel Estimations

Abstract: In the present globalized world, production forms are progressively divided across nations. Consequently, domestic consumption in one nation is progressively fulfilled by worldwide supply chains. This spectacle has pulled policy and widespread intellectual discussions on the assignment of greenhouse gas (GHG) emanations, especially carbon dioxide (CO2) emission; these are accountabilities connected to global trade since worldwide trade causes net carbon dioxide emission. The aim of the present study is to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
6
19
0
Order By: Relevance
“…In accordance with Zandi et al (2019), both economic development and trade liberalisation have negative and statistically significant impacts on CO 2 emissions. Energy consumption, population increase, and economic expansion are correlated with CO 2 emissions positively, according to a significant body of current research (Tiwari et al, 2013).…”
Section: Fdi Inflows and Carbon Emissionsmentioning
confidence: 81%
“…In accordance with Zandi et al (2019), both economic development and trade liberalisation have negative and statistically significant impacts on CO 2 emissions. Energy consumption, population increase, and economic expansion are correlated with CO 2 emissions positively, according to a significant body of current research (Tiwari et al, 2013).…”
Section: Fdi Inflows and Carbon Emissionsmentioning
confidence: 81%
“…Some researchers believe that trade liberalization reduces carbon dioxide emissions, and others hold the opposite view [22], based on the analytical framework of Grossman and Krueger [23], Chang and Chang [24] used four alternative measures to find that the relationship between trade liberalization and environmental quality also depends on country corruption. Oh and Bhuyan [25] studied the relationship between economic growth, energy consumption, trade liberalization and carbon dioxide emissions, they found that energy consumption has a positive effect on CO 2 emissions, but other variables have a positive effect only in the long run.…”
Section: Trade Liberalization and Carbon Dioxide Emissionsmentioning
confidence: 99%
“…They recommend that the government of Bangladesh support the appropriate policy to use alternative energy facilities that would not emit much CO 2 emission. Zandi et al (2019) investigate the effect of trade openness on CO 2 emissions. They implemented the panel data analysis for 105 developed and developing countries from the period of 1990-2017.…”
Section: Literature Reviewmentioning
confidence: 99%